Tradivox : Catholic catechism index - Bonner, Edmund; Seng, Aaron (Manchester, NH : Sophia Institute Press, 2020)
"Leaving aside the theological treatises and mystagogical sermon-cycles of many early fathers and doctors of the Church, there are concise works of systematic religious instruction that come down to us from even the ninth century, many having been written for a lay audience in Latin as well as translated into other spoken languages of the time. There are works in Old German such as the Weissenburg Catechism (ca. 800), the Frankish Liber Manualis of Dhuoda (ca. 842), the Elucidarium of Honorius (ca. 1096), and numerous works throughout the medieval period that served as catechisms "for simple folk"-all appearing well before Luther was born. Indeed, by the time the monumental Roman Catechism appeared in 1566, published as the first universal catechism for priests by order of the Council of Trent, the genre of Catholic catechisms was already long established, and populated by texts in every major language. Prior to the late Middle Ages, most Catholic catechisms were included within larger, sometimes multi-volume works of pastoralia: books intended for clergy to use in their work of shepherding souls. These texts often included directions for the assigning of suitable penances, admonitions for spiritual directees, relevant portions of canon law and liturgical rubrics, and other content helpful to parish priests in their daily tasks. In the thirteenth century, demand for concise manuals of instruction in doc- trine, morals, and prayer grew significantly, especially in the wake of the epochal Fourth Lateran Council (1215), which issued universal decrees regarding religious instruction for the faithful. Although the majority of publications in this period were authored for Catholic clerics, the laity also invested in copies for private study and home-based instruction, often posting portions of such works in public places for others to read. Given the typical brevity of medieval catechetical texts, this volume recovers four such works, alongside one of the major credal statements that was in frequent use at the time, each with a corresponding original manuscript image. The texts themselves are rendered here in English to show the continuity of Catholic doctrine as taught in those centuries, as well as to give an intriguing insight into the work of medieval parish priests, exhorted to "edify everyone with their knowledge both about the faith and about good behavior; and...[to] mold their subjects with the food of God's word according to how he inspires them, lest they are deservedly blamed because of their idleness.""--
Keywords: Theology, Doctrinal; Catholic Church